Effects of digestate application depth on soil nitrogen volatilization and vertical distribution - Lili, Wang; Wenzhe, Li; Zhongjiang, Wang; Zhiwu, Wang; Chao, Sui; Yan, Li (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: This study investigated the effect of the digestate application depth on soil nitrogen volatilization and vertical distribution in black loam soil and sandy loam column. The contents of soil moisture, TKN (total Kjeldahl nitrogen), ammonium nitrogen, nitrate nitrogen, and the extent of ammonia volatilization were tested by applying digestate at depths of 0 cm, 2 cm, 6 cm, 10 cm, 15 cm and 20 cm, respectively. The experimental results showed that ammonia volatilization mainly occurred in the first 10 days and reduced significantly when the application depth was deeper than 10 cm. At the same application depth, compared with the black loam, the nitrogen loss in sandy loam through ammonia volatilization was less, and the penetration depth of nitrate nitrogen and ammonium nitrogen were all deeper. In the same soil, nitrate nitrogen penetrated deeper than ammonium nitrogen at all application depths. Keywords: digestate, application depth, ammonia volatilization, black loam, sandy loam, soil nitrogen distribution DOI: 10.3965/j.ijabe.20160905.2396 Citation: Wang L L, Li W Z, Wang Z J, Wang Z W, Sui C, Li Y. Effects of digestate application depth on soil nitrogen volatilization and vertical distribution. Int J Agric & Biol Eng, 2016; 9(5): 101－107.